ANALISIS KANDUNGAN SERAT DAN UJI HEDONIK PADA PRODUK SNACK BAR TEPUNG BERAS MERAH (Oryza Nivara L) DAN KACANG HIJAU (Phaseolus Radiatus L) - Putri, Nanda Nathasya Yunica; Hermanto, Restu Amalia; Ulfah, Ardhika (Sekolah Tinggi Ilmu Kesehatan Holistik, 2020)
Background: The level of fiber consumption of Indonesian people is known to be low. Snack bars are snacks made from cereals and nuts that can be an alternative source of fiber. Research Objectives: To determine the effect of the ratio of brown rice flour and green beans to the hedonic test, fiber content, and the best formulation in making snack bars, and to determine the percentage of fiber contained in the snack bar compared to the nutritional adequacy rate (RDA). Methods: This study was a quantitative study using a completely randomized design with a ratio of brown rice flour and green beans in making snack bars. This study consisted of three stages, making snack bars, analyzing fiber content and hedonic test. The hedonic test was followed by 60 untrained panelists. Statistical analysis was performed using One Way Anova and kruskal wallis. Results: the snack bar fiber content of the three different formulas was not significantly different (p> 0.05) with p-value 0.055. The hedonic test results on color parameters obtained p-value 0.699, aroma with p-value 0.913, taste obtained p-value 0.762 and texture with p-value 0.708. Conclusion: The difference in the ratio of rice flour and green beans has no effect on fiber content and hedonic test on the snack bar.